Понятие произносительного стиля в современном языкознании - Жумыкина, А.А. (Культура народов Причерноморья, 2014)
Статья посвящена рассмотрению проблемы социально детерминированной
вариативности речи, актуальность которой обусловлена интересом языковедов к вопросам
социолингвистической вариативности с учетом комплекса внеязыковых факторов, определяющих выбор
говорящим того или иного произносительного стиля, а также проблеме стратификации
произносительных стилей и отсутствия единой общепринятой классификации фоностилей. Стаття присвячена розгляду проблеми соціально детермінованої варіативності мовлення,
актуальність якої зумовлена інтересом лінгвістів до питань соцiолiнгвiстичної варіативності,
зумовленої комплексом позамовних чинників, визначаючих вибір мовцем того чи іншого вимовного
стилю, а також проблеми стратифікації вимовних стилів і відсутності єдиної загальноприйнятої
класифікації фоностилів. One of the topical issues in modern sociolinguistics is the language variability which, being socially
deterministic, is traced at all levels of the language system.
Timeliness of the paper is determined by linguists’ interest in language variability with due regard to a range of
extralinguistic factors designating a speaker’s choice of a certain speech style as well as the problem of speech
styles stratification and lack of a universal generally accepted classification.
Socially determined speech variability is characterized in terms of two dimensions – stratification and
situational ones. Social stratification of the speech is the result of its inextricable connection with the structure
of society and thus is marked by discrepancies between lingual and speech means inherent in representatives of
particular social strata and groups. Situational aspect of speech variability is manifested in pre-eminent use of
specific lingual and speech means depending on a number of circumstances of a social situation and speakers’
emotional states.
The point to be emphasized is that both types of variability tightly correlate as differences associated with the
structure of society overlap distinctions imposed by social situation.
A set of stratification and situational peculiarities determine the use of particular phonetic styles.
Although scientists single out different number of phonetic styles and there is no prevailing conventional speech
styles classification, all existing classifications base themselves upon phonetic variability at segmental and
prosodic levels provided by extralinguistic social-psychological factors, such as communicant’s social
background and status, age, gender, speakers’ relations, communication spheres, speech situation, aims of
intercourse, conversation subject matter, speaker’s mood and emotional state, etc.